Relação entre as forças internas e externas na inovação em serviço na atenção primária à saúde - Rasia, Isabel Cristina Rosa Barros (My University, 2016)
This thesis focuses on the innovation in services at Health Primary Attention (HPA) andaims at analyzing the relationship between internal and external forces in the innovation in services at HPA in Pelotas, describing its organization and management ways, the procedures established for innovating, its guidance on the HPA, and the innovation generated/produced on the following dimensions: product, process, marketing, and organizational area (Manual de Oslo, 2005). Each dimension was analyzed under perspectives as follows: physical structure, human resources, appliances, medicines and materials, access to complementary examinations, management, and user service. Innovation on health services assumption is the improvement of production and efficiency, the increase on quality and responsiveness, the reduction on variation in care practice, and the increase of access to health services. The HPA includes the individual’s, family, and collectivity first level of contact with the health system. Research was performed through a cross-sectional, objective, exploiting method under a quantitative, qualitative nature of approach. A case study was conducted by the application of an empirical research to the population of managers linked to the health system of the local HPA asking about the health system forming, innovation in services, and its guidance on the HPA according to the Primary Care Assessment Tool, a tool validated by Starfield (2001) and (2010).Quantitative results show that the innovation in services were, as to their typology, mostly: product (98%), process (90%), and organizational (88%), and fewest in marketing (32%). In all dimensions, the perspectives presenting more innovations were connected to management, user care, and human resources. Regarding to “HPA orientation” outcome, the general average 6.91 (SD = 1,12) indicated that the local “UBS” are arranged in HPA. However, when stratified according to the attention model, the “UBS” working with the Family Health Strategy (FHS) scored 7.51 (SD = 0.71),while Traditional ones averaged 5.91 (dp = 0.95), considered as not guided in HPA (p = 0,000). As to the association of innovations and orientation in HPA it was seen under the gross analysis by Poisson Regression that they belong to the model that pays attention to FHS variables, which were significantly related to the orientation in HPA. In the adjusted analysis, however, only the variable attention model remained related to the outcome (2.86; IC 95% 2.18 – 6.91). The qualitative analysis identified that the county performs the full management model of its Municipal Health System and the processes of innovation in services are leveraged by the Federal Government, being the programs and projects launched at national level, along with the Municipal Secretariat of Health, developed with the effective participation of health teams from the Basic Unit of Health (BUH), based on planning and formalization, supported by the assigned community, Universities, Municipal Council of Health (MCH), and the Local Council of Health (LCH).
Esta Tese tem, como tema central, a inovação em serviço na Atenção Primária à Saúde (APS) e, como objetivo, analisar a relação entre as forças internas e externas na inovação em serviço na APS de Pelotas, caracterizando a sua forma de organização e gestão, os processos estabelecidos para inovar, sua orientação em APS e as inovações geradas/produzidas nas dimensões: produto, processo, marketing e organizacional (Manual de Oslo, 2005). Cada dimensão foi analisada nas perspectivas:estrutura física, recursos humanos, equipamentos, medicamentos e materiais, acesso a exames complementares, gestão e atendimento ao usuário. Inovações em serviços de saúde têm como premissa, a melhoria da produtividade e eficiência, o aumento da qualidade e da capacidade de resposta, a redução das variabilidades na prática assistencial e a ampliação do acesso aos serviços de saúde. A APS compreende o primeiro nível de contato dos indivíduos, da família e da coletividade, com o sistema de saúde. O método de investigação teve um delineamento transversal, objetivo exploratório e, quanto à natureza de abordagem quantitativa e qualitativa. Realizou-se um estudo de casos com a aplicação de pesquisa empírica à população de gestores ligados ao sistema de saúde da APS da cidade com perguntas sobre a conformação do sistema de saúde, a inovação em serviços e sua orientação em APS de acordo com o Primary Care Assessment Tool, instrumento validado por Starfield (2001) e Brasil (2010). Os resultados quantitativos demonstram que as inovações em serviços eram, em maioria da tipologia produto (98%), processo (90%), e organizacional (88%) e em menor proporção a de marketing (32%). Em todas as dimensões, as perspectivas com mais inovações estavam ligadas à gestão, atendimento ao usuário e recursos humanos. Em relação ao desfecho “Orientação em APS”, a média geral de 6,91 (dp = 1,12) demonstrou que as UBS do município estão orientadas em APS.Contudo, quando se estratifica por modelo de atenção, as UBS que trabalham com a Estratégia de Saúde da Família (ESF) estão orientadas com escore de 7,51 (dp = 0,71), enquanto que as Tradicionais obtiveram uma média de 5,91 (dp = 0,95), consideradas não orientadas em APS (p = 0,000). Quanto à associação das inovações e à orientação em APS, constatou-se na análise bruta por Regressão de Poisson, pertencer ao modelo de atenção às variáveis ESF, ter planejamento de ações e organização formal das atividades, as quais estiveram significativamente associadas à orientação em APS.No entanto, na análise ajustada, apenas a variável modelo de atenção permaneceu associada ao desfecho (2,86; IC 95% 2,18 – 6,91). A análise qualitativa identificou que o município atua sob o modelo de gestão plena do Sistema Municipal de Saúde e os processos de inovação em serviço são alavancados através do Governo Federal, sendo os programas e projetos lançados a nível nacional, com a adesão da Secretaria Municipal de Saúde (SMS), desenvolvidos com a participação efetiva das equipes de saúde das Unidades Básicas de Saúde (UBS), através do planejamento e da formalização, amparadas pela comunidade adscrita, Universidades, Conselho Municipal de Saúde (CMS) e Conselho Local de Saúde (CLS).
Keywords: Cuidados primários de saúde - Inovações tecnológicas; Serviços de saúde - Administração; Saúde pública - Brasil; Primary health care - Technological innovations; Health services administration; Public health